2015
DOI: 10.1002/oby.21029
|View full text |Cite
|
Sign up to set email alerts
|

Irisin levels before and after physical activity among school‐age children with different BMI: A direct relation with leptin

Abstract: Objective: Irisin is a novel myokine that seems to mediate the beneficial effects of exercise. Levels of circulating irisin before and after an 8-month physical activity program (PAP) in school-age children were evaluated. Methods: Irisin and leptin were measured at baseline and at follow-up among 85 children with different BMI. Results: Of the 85 children (mean age 8.9; 47% female), 25 children had normal weight, 23 were overweight, and 37 had obesity. We observed no significant difference in irisin serum lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 18 publications
8
45
4
4
Order By: Relevance
“…Notably, Stengel et al reported lower plasma irisin in anorexic adult patients and a linear relationship between the irisin levels and BMI in adults [8], similar to our finding in children with underweight status. Moreover, a recent study by Palacios-González et al [14] showed higher levels of circulating irisin in obese children and a positive correlation with BMI, also in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Notably, Stengel et al reported lower plasma irisin in anorexic adult patients and a linear relationship between the irisin levels and BMI in adults [8], similar to our finding in children with underweight status. Moreover, a recent study by Palacios-González et al [14] showed higher levels of circulating irisin in obese children and a positive correlation with BMI, also in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The underweight group showed the highest proportion of body muscle mass to fat mass, followed by the normal weight, overweight, and obese groups, in this order. The different body composition of each group might account for the variations in the irisin plasma levels, but this relationship remains to be defined for children [14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous cross-sectional studies reported associations between irisin and anthropometric or biochemical parameters (10-12), other myokines (13), and adipokines such as adiponectin (14). Studies in children and adolescents have shown that irisin is regulated in a sex-dimorphic manner (15), is positively associated with BMI and leptin (16), and is increased after a 1-year lifestyle intervention program that resulted in significant weight-loss and improvement of other clinical parameters (17). In a longitudinal interventional study, irisin levels were higher in obese children with impaired glucose metabolism and This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that irisin is not only a myokine, but it is also an adipokine, 62 and plasma irisin levels are unexpectedly higher in obese humans. 63, 64 Furthermore, Viitasalo and colleagues 65 found a positive and unfavourable correlation between plasma FFAs and irisin in overweight children. More reliable and sensitive detection methods and greater in depth study of the mechanistic regulation of irisin are required to establish whether irisin is indeed a mediator of pathways that propagate obesity, or whether irisin has potential as a therapeutic target for treating or managing obesity.…”
Section: Modulation Of Beige Adipocyte Formation In Human Interventiomentioning
confidence: 98%